2018
DOI: 10.14260/jemds/2018/793
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Seroprevalence and Changing Trend of Dengue in a Tertiary Care Hospital in Manipur

Abstract: BACKGROUND Dengue fever is a seasonal and emerging acute mosquito borne arbo-viral illness affecting tropical and subtropical countries. This illness ranges from mild asymptomatic form to severe dengue haemorrhagic fever with or without dengue shock syndrome. In India, the epidemiology of dengue virus infection is very complex and ever changing. Infection has expanded over the last two decades to all regions of the country including hilly states of the northeastern region (Assam, Arunachal Pradesh, Nagaland an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Most of studies from India [18,24,40,51,56] and Nepal [19,23,29,32,41,43,61,64] show almost consistent seasonality of DEN outbreaks, lasting from June to December. The majority of the studies from India and Nepal reported maximum DEN cases in September, October, and November in the postmonsoon period [18][19][20][23][24][25][27][28][29][39][40][41][42][43]54,61,62]. Our findings concerning a seasonal distribution of DEN in HKH countries are similar to the studies on Brazil [91] and Thailand [92].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Most of studies from India [18,24,40,51,56] and Nepal [19,23,29,32,41,43,61,64] show almost consistent seasonality of DEN outbreaks, lasting from June to December. The majority of the studies from India and Nepal reported maximum DEN cases in September, October, and November in the postmonsoon period [18][19][20][23][24][25][27][28][29][39][40][41][42][43]54,61,62]. Our findings concerning a seasonal distribution of DEN in HKH countries are similar to the studies on Brazil [91] and Thailand [92].…”
Section: Discussionsupporting
confidence: 86%
“…In the HKH region, DENV was first recognized in tea gardens of Northern Assam, India, in 1951 [74]. According to the literature, a large number of states (eight states and two provinces) in the Himalayan and sub-Himalayan region of India have been affected by DEN after 2005 onwards [18,20,21,24,25,27,28,33,36,39,40,42,50,51,54,56,57,60,62,65,71,72,74] The virus circulating in India in the 1950s, causing mild diseases, was replaced or evolved into genotypes with bigger virulence and transmissibility [82]. The movement of the human population from DEN-endemic areas of India to nonendemic areas might have significantly contributed to the outbreak of DEN in new areas and more frequent DEN epidemics after 2005 [57].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations